2017
DOI: 10.1038/s41598-017-16471-6
|View full text |Cite
|
Sign up to set email alerts
|

Toughness amplification in copper/epoxy joints through pulsed laser micro-machined interface heterogeneities

Abstract: This work addresses the mechanics of debonding along copper/epoxy joints featuring patterned interfaces. Engineered surface heterogeneities with enhanced adhesion properties are generated through pulsed laser irradiation. Peel tests are carried out to ascertain the effect of patterns shape and area fraction on the mechanical response. Experimental results are evaluated with the support of three-dimensional finite element simulations based on the use of cohesive surfaces. Results discussion is largely framed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Joining two dissimilar materials through a patterned interface is indeed a well-known strategy to improve the failure resistance of bimaterial attachments, and numerous works have investigated this topic considering engineering materials ( Cordisco et al, 2012 ; Caimmi and Pavan, 2009 ; Hernandez et al, 2017 ; Kim et al, 2010 ; Yao and Qu, 2002 ). In this context, one interesting research question is about the relationship between the interface geometrical properties and the corresponding interfacial fracture toughness.…”
Section: How To Link Microstructure and Composition To Mechanical Properties?mentioning
confidence: 99%
“…Joining two dissimilar materials through a patterned interface is indeed a well-known strategy to improve the failure resistance of bimaterial attachments, and numerous works have investigated this topic considering engineering materials ( Cordisco et al, 2012 ; Caimmi and Pavan, 2009 ; Hernandez et al, 2017 ; Kim et al, 2010 ; Yao and Qu, 2002 ). In this context, one interesting research question is about the relationship between the interface geometrical properties and the corresponding interfacial fracture toughness.…”
Section: How To Link Microstructure and Composition To Mechanical Properties?mentioning
confidence: 99%
“…Indeed, current lasers are provided with high-precision beam positioning systems, which ensure the ability to treat the target surfaces selectively, and with fairly accurate geometrical control. 32…”
Section: T-jointsmentioning
confidence: 99%
“…Pulsed laser irradiation has recently become useful in surface treatment of CFRP because it improves bonding. Hernandez and Tao [3,5] pointed out that, indeed, pulsed laser irradiation modifies both the surface chemistry and the morphology of adherend surfaces. Although several studies [6][7][8] showed that UV laser treatment increased the secondary bonding strength of CFRP composites, Tao et al [2] confirmed that pulsed CO2 laser irradiation improved adhesion while offering faster-processing speed, which is essential during the construction of large structures.…”
Section: Introductionmentioning
confidence: 99%